CEO compensation and ownership structure in Chinese real estate listed companies - YU, HAN (2019)
This study examines the relationships between CEO compensation and firm financial performance under different ownership structures. This dissertation mainly focuses on state ownership and foreign ownership. Due to China is a developing country and partially privatized, state ownership plays an important role in corporate governance. In addition, with the increase in international investment in recent years, foreign investors should be concerned. 124 Chinese real estate listed companies are used to investigate the pay-performance relation from 2014 to 2018. There are five explanatory variables in panel data regression, including ROA, Top1, Top 10, D_State and D_Foreign.